Pinch Hitter: The Effectiveness of Content Summaries Delivered by a Guest Lecturer in Online Course Videos - Fanguy, Mik; Costley, Jamie; Baldwin, Matthew (International Review of Research in Open and Distributed Learning, 2017)
Lecture videos have become an increasingly prevalent and important source of learning content. Lecturer-generated summaries may be used during a video lecture to improve student recall. Furthermore, the integration of a guest lecturer into the classroom may be a beneficial educational practice drawing the learner’s attention to specific content or providing a change of pace. The current study measures the effects of lecturer-generated summaries and the inclusion of a guest lecturer on students’ ability to recall online video lecture contents. Seven sections of a flipped scientific writing course were divided into three groups. The control group videos featured a lecturer speaking with PowerPoint slides in the background. The Summaries Only group viewed the same videos as those of the control, with the addition of lecturer-generated summaries spliced into the middles and ends of the videos, respectively, and these summaries were delivered by the same lecturers of the original video. The Summaries with a Guest Lecturer group viewed the same videos as the control, but with the addition of lecturer-generated summaries respectively spliced into the middles and ends of the videos, and these summaries were instead delivered by a guest lecturer. Student recall was measured through two online multiple-choice quizzes. The results of the study show that the Summaries Only group significantly outperformed the other two groups, while no significant difference was found between the performances of the control and the Summaries with a Guest Lecturer group. The results suggest that lecturer-generated summaries help to improve student recall of online video lecture contents. However, the introduction of a guest lecturer shown in a different setting may cause learners to lose concentration, nullifying the benefit of the summaries.